The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3892/etm.2013.1037
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in visual function and quality of life following a blindness prevention surgery program in a rural area of Eastern China

Abstract: The aim of this study was to assess the changes in visual function (VF) and quality of life (QOL) among patients following blindness prevention surgery in a rural area of Eastern China. The prospective study selected cataract patients via mobile eye screening camps. VF and QOL questionnaires originally developed by Fletcher et al were completed prior to and 6 months after surgery. Small-incision cataract surgery (SICS) with posterior chamber intraocular lens (IOL) implantation was performed on patients by a bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
4
5
0
Order By: Relevance
“…In addition, mothers of blind children comparing to those of autistic and of normal functioning ones, in general quality and social interactions subscales, had higher QoL, whereas in independency subscale, they scored lower QOL. The results were in agreement with findings from earlier reports (13,18,19) The higher QoL for mothers of blind children in general quality and social interaction subscale could be explained based on their children behaviors. In fact, blind kids, as compared to autistics, have more individual and social activities, and in some cases they have similar interest to what normal-functioning children do, such as learning music, painting, learning second language, etc.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, mothers of blind children comparing to those of autistic and of normal functioning ones, in general quality and social interactions subscales, had higher QoL, whereas in independency subscale, they scored lower QOL. The results were in agreement with findings from earlier reports (13,18,19) The higher QoL for mothers of blind children in general quality and social interaction subscale could be explained based on their children behaviors. In fact, blind kids, as compared to autistics, have more individual and social activities, and in some cases they have similar interest to what normal-functioning children do, such as learning music, painting, learning second language, etc.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the fact that almost a third of the whole machinery of the sensory connection system is made of visiualrelated pathways, people could be described as visual beings. Hence, vision impairment causes people to experience disability ever more that loss of other sensory modalities (13)(14)(15).…”
Section: According To the Diagnostic And Statisticalmentioning
confidence: 99%
“…Before surgery, most participants had poor VA and consequently a low VF and QoL score, given the significant relation between VA and VFm and QoLm scores. Before surgery, the general, visual perception and peripheral vision subscales were the most affected in VF, corroborating the results found by Fletcher et al [ 10 ], while for Zhou et al [ 15 ] in addition to the general subscale, depth perception and sensory adaptation were more affected. Regarding QoL, the mental, mobility and social subscales were more affected, and similar results were found by Fletcher et al [ 10 ], whose mobility and social were more affected, and by Zhou et al [ 15 ], whose mental and mobility scores were lower, which demonstrates the impact of cataract, especially in the mobility aspect.…”
Section: Discussionsupporting
confidence: 88%
“…These questionnaires were validated and used in a clinical trial of cataract surgery in India [ 9 , 10 ], and later used in other studies in countries such as Nigeria [ 11 , 12 ], Mali [ 13 ], Pakistan [ 14 ] and China [ 15 , 16 ], and were considered suitable for use in Pakistan’s national research because they are concise and their administration overcomes the difficulty of illiteracy [ 14 ]. This phase took place between October 2019 and March 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Also in this regard a study conducted by Mahmoud &Monsudi, (2012), reported that 45.6%patients were peasant farmers (36) . On the other hand, a study conducted by Valero et al (2007), who investigated the relationship between sunlight exposure and risk of cataract and they found that no association was found between years of outdoor exposure and risk of cataract (40) .…”
Section: Discussionmentioning
confidence: 99%